1998
DOI: 10.1073/pnas.95.2.460
|View full text |Cite
|
Sign up to set email alerts
|

The importance of tRNA backbone-mediated interactions with synthetase for aminoacylation

Abstract: We have identified six new aminoacylation determinants of Escherichia coli tRNA Gln in a genetic and biochemical analysis of suppressor tRNA. The new determinants occupy the interior of the acceptor stem, the inside corner of the L shape, and the anticodon loop of the molecule. They supplement the primary determinants located in the anticodon and acceptor end of tRNA Gln described previously. Remarkably, the three-dimensional structure of the complex between tRNA Gln and glutaminyl-tRNA synthetase shows that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…A: tRNA of the complex with the synthetase shown in the same orientation as in C+ Small spheres: 29-hydroxyl groups; large spheres (red): critical positions with sequence number+ B: As A, but critical pro Rp-oxygens are in green+ C: Three-dimensional representation of the interaction between tRNA (yellow) and the synthetase (blue) based on the crystal structure of the yeast tRNA Asp complex (Cavarelli et al+, 1993)+ Spheres: phosphate-backbone of tRNA and carbon main-chain atoms of the protein+ experiments for the aminoacylation of tRNA Gln (McClain et al+, 1998)+ In conclusion we have analyzed for the first time full length tRNA transcripts for individual positions where the presence of 29-hydroxyl groups is essential for charging and where phosphates can not be replaced by phosphorothioates+ The degree of reduction in charging efficiency caused by single 29-deoxy and phosphorothioate substitutions is small+ However, multiple occurrences of 29-deoxy substitutions generally leads to complete loss of charging+ The general agreement between the X-ray and interference analyses is encouraging with respect to applying the latter method to the study of other RNA-protein interactions+…”
Section: Discussionmentioning
confidence: 99%
“…A: tRNA of the complex with the synthetase shown in the same orientation as in C+ Small spheres: 29-hydroxyl groups; large spheres (red): critical positions with sequence number+ B: As A, but critical pro Rp-oxygens are in green+ C: Three-dimensional representation of the interaction between tRNA (yellow) and the synthetase (blue) based on the crystal structure of the yeast tRNA Asp complex (Cavarelli et al+, 1993)+ Spheres: phosphate-backbone of tRNA and carbon main-chain atoms of the protein+ experiments for the aminoacylation of tRNA Gln (McClain et al+, 1998)+ In conclusion we have analyzed for the first time full length tRNA transcripts for individual positions where the presence of 29-hydroxyl groups is essential for charging and where phosphates can not be replaced by phosphorothioates+ The degree of reduction in charging efficiency caused by single 29-deoxy and phosphorothioate substitutions is small+ However, multiple occurrences of 29-deoxy substitutions generally leads to complete loss of charging+ The general agreement between the X-ray and interference analyses is encouraging with respect to applying the latter method to the study of other RNA-protein interactions+…”
Section: Discussionmentioning
confidence: 99%
“…Determinants facilitate aminoacylation; antideterminants impede it. Their combined effect ensures that a particular tRNA is a substrate for its cognate synthetase and not a substrate for all the other synthetases present in a cell (McClain 1993;Nureki et al 1994;Giegé et al 1998;McClain et al 1998;Beuning and Musier-Forsyth 1999;Fender et al 2004). An updated list of determinants based on a compilation by Giegé et al (1998) is shown in Supplemental Table S1.…”
Section: Introductionmentioning
confidence: 99%
“…Here we demonstrate the feasibility of an assay that directly measures the fraction of aminoacylated tRNA by its altered mobility on an acidic, denaturing polyacrylamide gel+ Such gels have been used to estimate the levels of aminoacylated tRNA in vivo (Varshney et al+, 1991;McClain et al+, 1998), and to detect selfaminoacylation by a ribozyme (Illangasekare et al+, 1997)+ However, initial experiments revealed that the resolution of these gels was not sufficient to obtain accurate kinetic data when intact tRNA was used+ Thus, we employed a tRNA made of two RNA fragments with a nick at a position near the 39 terminus that does not affect aminoacylation kinetics (Liu & Musier-Forsyth, 1994)+ Because this assay uses high-specific activity [ 32 P]-labeled tRNA and measures aminoacylation directly, it overcomes the major shortcomings of the tritiated amino acid assay and should be valuable for structure-function studies+…”
Section: Introductionmentioning
confidence: 99%